Peningkatan Kemampuan Menulis Teks Fabel Menggunakan Model Pembelajaran Creative Problem Solving (CPS) Siswa Kelas VII MTs Al-Quran Harsallakum Kota Bengkulu - Rilla Wahana; Susetyo Susetyo; Gumono Gumono (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to describe the improvement of the ability to write fable texts using the Creative Problem Solving (CPS) learning model for seventh grade students of MTs Al-Quran Harsallakum Bengkulu City. The research method used is the Classroom Action Research (CAR) method with the Hopkins model. This study consisted of two cycles, each cycle consisting of four stages, namely, planning, implementing, observing, and reflecting. The technique of collecting data uses test, observation, and observation techniques. The data analysis technique in the study was to provide a value or score on the fable text written by students, as well as an assessment of the activities of students and teachers in learning to write fable texts carried out by researchers and peers. The results showed that there was an increase in teacher activity cycle I 87.50% to 100%. Student activity also increased in the first cycle based on obeserver observations, namely 4.56% and the rater at 4.22%. Whereas in the ability to write fable text for students of class VII.G MTs Al Quran Harsallakum Bengkulu City experienced an increase in writing fable texts using the Creative Problem Solving (CPS) learning model, seen in cycle I the average score of students was 73.15 with a sufficient category. and increased in cycle II with an average value of 84.35 good category.